THE RELEVANCE OF ACCOUNTING FOR BUSINESS MANAGEMENT OF INDIVIDUAL MICRO-ENTREPRENEURS - MEIS IN THE STATE OF TOCANTINS (REMUNOM, 2025)
This research sought to highlight the importance of accounting as a management tool for Individual Microentrepreneurs (MEIs). MEIs represent a fundamental pillar of the Tocantins economy, driving regional development and generating employment and income. However, despite their socioeconomic importance, these businesses face high mortality rates, often associated with a lack of appropriate management practices, particularly the limited use of accounting as a strategic tool. The main objective of this work was to analyze the relevance of accounting as a financial control and management support tool for MEIs in Tocantins. The study, of a bibliographic and documentary nature, is based on analyses of scientific articles, books, theses, and reports to demonstrate the effectiveness and contribution of accounting practices to these businesses. Given the current economic climate, there is significant growth in entrepreneurship in Brazil, with MEIs playing a significant role in job creation and economic growth, especially in regions with less access to formal opportunities, such as the state of Tocantins. Despite their significant contribution, many MEIs struggle to remain active and competitive, often due to a lack of appropriate management practices. The results show that MEIs' lack of specific technical knowledge makes accounting an essential tool to fill this gap. Therefore, the role of accounting and its ramifications is crucial in assisting decision-making, offering technical support that these entrepreneurs lack, highlighting how its application can be a differentiator for the sustainability and growth of these businesses.